Building international investment law the first 50 years of ICSID - Kinnear, Meg N.; Fischer, Geraldine R.; Mínguez Almeida, Jara; Torres, Luisa Torres; Uran Bidegain, Mairée (Kluwer Law International, 2016)
"This volume celebrates the first 50 years of ICSID by presenting the landmark cases that have been decided under its auspices. These cases have addressed every aspect of investment disputes: jurisdictional thresholds; the substantive obligations found in investment treaties, contracts, and legislation; questions of general international law; and a number of novel procedural issues. Each chapter, written by a knowledgeable expert on the chapter?s particular focus, looks at an international investment law topic through the lens of one or more of these leading cases, analysing what the case held, how it has been applied, and its overall significance to the development of international investment law."--Publisher's website.